Who are the entrepreneurs? A case for accelerated service economy for agricultural machinery in Odisha - Singh, Vartika; Ward, Patrick S.; Gupta, Shweta; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2018)
In this note, we discuss the traits of machine owners that are associated with entrepreneurial behavior and ways in which information about these traits could be used to improve the targeting of mechanization subsidies to better foster the emergence of custom-hire services for farm machinery in Odisha.